ANALISIS KEKERABATAN TANAMAN KELENGKENG (Dimocarpus longan) DAN KELENGKENG MATA KUCING (Dimocarpus longan ssp. malesianus Leenh.) ASAL KECAMATAN PERANAP BERDASARKAN PENANDA RAPD (RANDOM AMPLIFIED POLYMORPHIC DNA) - Rinda Anggini; Dewi Indriyani Roslim; Adiwirman (UIR Press, 2024)
Longan (Dimocarpus longan) is a fruit-bearing plant that thrives in subtropical and tropical regions, including Indonesia. The cat's eye longan (Dimocarpus longan ssp. malesianus Leenh.) is a subspecies of the longan. This study's objective is to explore the genetic relationship between longan and cat's eye longan through RAPD markers. The research involved several steps: collecting samples, isolating DNA, conducting DNA electrophoresis, performing PCR, and analyzing data. The analysis was carried out using the UPGMA (Unweighted Pair Group Method with Arithmetic Average) method, facilitated by MVSP 3.22 software. DNA isolation was performed on 18 individuals of longan and cat's eye longan, utilizing the Genomic DNA Mini Kit Plant (Geneaid). The primers employed in this study included OPD-08, D-08, X-01, and OPJ-20. Results indicated that a total of 40 RAPD bands were generated from the longan and cat's eye longan samples using the four primers. The OPD-08 primer yielded the largest number of bands, measuring 2500 bp. The highest similarity coefficient of 77.78% was observed between genotypes MK3 and MK4, while the lowest similarity values were noted in various pairs, including K2 and MK9, K3 and MK1, K3 and MK2, and K3 and MK6, all at 0.000%. The genetic relationship percentage between longan and cat's eye longan was found to be 36%. This indicates that they are genetically distinct and not closely related. Thus, the findings confirm a lack of close genetic affinity between the two.